Phytoplankton community of the Itaya river basin in Loreto, Peru - Ismiño, Rosa (2018)
The phytoplankton community was evaluated in 21 samples collected in seven sites in the Itaya river basin. In total, 70 species belonging to 40 genera, 21 families and 6 divisions were identified. The most abundant group was Bacillariophytas (51%), followed by Chlorophytas (31%), Euglenophytas (11%), Cyanophytas (5%), and others (2%) corresponding to Xanthophyta and Chrysophyta. The best represented species were Surirella ovalis, Navicula sp and Pinnularia sp. For this ecosystem, the density was between 100 to 13 000 ind/l-1 (individuals per litre) out of a total of 24 500 ind/l-1, with a richness of 11 to 27 species and an abundance of 23 to 55 individuals. The analysis of diversity according to Shannon-Wiener was from 7.26 to 25 units of effective species, with an equity of Pielou of 0.84-0.97, which indicates that the populations were homogeneous. Regarding the similarity index, it shows that the phytoplankton communities were formed by three groups with a similarity of 35%. According to the diatomic index (IDG), it is concluded that the water of the Itaya river could be contaminated at the sampling points.